Tindak Pidana Penggelapan Dalam Jabatan Dilakukan Oleh Sales Executive Hotel The Hill Sibolangit Medan (Studi Kasus Putusan Nomor : 1170/Pid.B/2016/PN. Mdn) - Edianto Sihaloho; Ridho Mubarak; Riswan Munthe (Universitas Medan Area, 2020)
The use of criminal law efforts as an effort to overcome social problems, including in the field of law enforcement policies to achieve the welfare of society in general. These developments have greatly influenced various parties / persons to carry out various ways in fulfilling their wishes, one of which is the embezzlement of the position stipulated in Article 374 of the Criminal Code. This study aims to determine the forms of embezzlement in the criminal law. The method used in this research is normative juridical and conducting direct interviews with the Judges involved in the decision based on the decision number: 1170 / Pid.B / 2016 / PN. MDN. The result of the research is that this form of embezzlement takes place in a position, that is, misusing an existing position Factors that cause embezzlement based on data obtained in general is the decline in employee mentality is one of the factors that cause embezzlement. The application of the criminal sanction of embezzlement in a position must first be seen from its elements. Where the penalty that can be imposed is contained in Article 374 of the Criminal Code.